Ketergantungan masyarakat Dayak terhadap hutan di sekitar Taman Nasional Kayan Mentarang - Uluk, A.; Sudana, M.; Wollenberg, Eva Karoline (Center for International Forestry Research, 2001)
In Indonesia, rapid deforestation is affecting local populations’ access to forest, yet little information is available about the impacts of deforestation on highly forest-dependent populations. To better understand these potential impacts, this document reports on economic and cultural uses of the forest for three villages in the Sub-District of Pujungan in East Kalimantan, using data from household suveys conducted in 1996. It shows how local Kenyah groups depend on forests for food, medicine, construction, cash income, as well as to maintain natural resources such as water and soil fertility, and as a source of cultural symbols and even people’s names. It also show the linkages of the forest to Kenyah culture and reviews local rules of use of forest resources, including the concept of tana’ ulen. The study notes that despite policies making customary management of forest possible, these policies have yet to be formally applied in area. Until the local communities feel more secure about their rights to land, their way of life, which depends so very much on the forest, is at risk.